Training medical students as basic life support instructors: a demonstrative method pilot study - Fernández Florido, Pedro; Parrilla Ruiz, Francisco Manuel; Rodríguez Fernández de Simón, Teresa; Álamo García, Lydia; Gómez Moreno, Gerardo; Pérez Villares, José Miguel; Cárdenas Cruz, Antonio (Frontiers in Medicine, 2025)
IntroductionTraining the general population in basic life support is essential because it increases the likelihood that laypeople will perform high-quality cardiopulmonary resuscitation early on, which has a significant impact on patient outcomes. The university stage is a pivotal time to impart this knowledge to individuals outside the healthcare sector. This study aims to describe and analyses the extent to which students on the Medicine degree programme at the University of Granada have acquired competencies in teaching methodology applied to life support instruction. Additionally, the study aims to evaluate the potential academic and social impact of this training intervention.MethodsThis is a prospective observational study targeting a selected group of medical students from the University of Granada. The students received specific training in teaching methodology applied to basic life support teaching and learning processes. The students' acquisition of various skills is assessed to determine their readiness to become trainers in this field.ResultsA total of 89 students, all in their third to fifth year of university, received training in the methodology applied to teaching and learning processes in basic life support. This training used the different phases of the demonstrative method. Four training sessions were conducted, during which the phases of the demonstrative method were explained in detail and the students were given the opportunity to carry them out. The performance of the entire process was then assessed. As a result, over 89% of students successfully completed the phases of the demonstrative method.DiscussionMedical Degree students are capable of acquiring skills in teaching methodology to conduct Basic Life Support training courses for the general population. This is independent of the year in which they are in their training, as long as they have received theoretical training in this subject. Further studies are encouraged by these results, with the aim of extending this type of training to other medical education centers nationwide.